Model Pengembangan Kurikulum KKNI pada PTKIS Berbasis Pesantren - Sunoko, Ahmad; Ma'rifah, Siti (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2024)
The development of higher education curricula in Indonesia faces challenges in adapting to globalization, technological advancements, and industrial demands while preserving local and religious values. This study analyzes the curriculum development model based on the Indonesian National Qualification Framework (KKNI) at Islamic higher education institutions with a pesantren-based approach, using STAI Al-Anwar Sarang Rembang as a case study. It identifies key issues such as limited human resources understanding KKNI concepts, insufficient expert guidance, and inadequate budgets and infrastructure as major obstacles to curriculum implementation. The research employed a qualitative approach with a case study design, involving in-depth interviews, participatory observations, and analysis of institutional documents. Data were analyzed through data reduction, presentation, and conclusion drawing. The findings reveal that integrating pesantren values with KKNI-based learning outcomes has been collaboratively designed, although implementation remains suboptimal. Major challenges include a lack of training for lecturers, limited information technology infrastructure, and unsystematic evaluations. However, the study also highlights significant potential for curriculum improvement through expert support, regular training, and enhanced infrastructure. This research provides significant implications for curriculum development in pesantren-based institutions by emphasizing the importance of a holistic approach that integrates traditional education with modern demands. In conclusion, despite numerous challenges, the KKNI-based pesantren curriculum holds great potential to produce graduates who are academically competent, professionally skilled, and deeply rooted in strong moral values.